2001
DOI: 10.1099/00221287-147-7-1929
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic structure of Shiga-toxin-2-encoding phages isolated from Escherichia coli O157:H7 indicates frequent gene exchange between lambdoid phage genomes

Abstract: Shiga-toxin-2 (stx 2 )-encoding bacteriophages were isolated from Norwegian Escherichia coli O157 :H7 isolates of cattle and human origin. The phages were characterized by restriction enzyme analysis, hybridization with probes for toxin genes and selected phage DNA such as the P gene, integrase gene and IS1203, and by PCR studies and partial sequencing of selected DNA regions in the integrase to stx 2 region of the phages. The stx 2 -phage-containing bacteria from which inducible phages were detected produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 29 publications
7
68
0
1
Order By: Relevance
“…Alternatively, APSE-encoded toxins may target and destroy the cells of attacking parasitoids or other eukaryotic enemies, thereby protecting their aphid hosts. The mosaic structure of APSE genomes, also observed in other lambdoid phage (20), reflects recombination among haplotypes and could promote hypervariability in toxin-encoding capacity of H. defensa isolates. Thus, the phages may enable H. defensa to mount a varied arsenal of toxins to defend aphid hosts against natural enemies, which vary among populations and over time (e.g., refs.…”
Section: The Apse-h Defensa-aphid Consortium As a Complex Mutualisticmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, APSE-encoded toxins may target and destroy the cells of attacking parasitoids or other eukaryotic enemies, thereby protecting their aphid hosts. The mosaic structure of APSE genomes, also observed in other lambdoid phage (20), reflects recombination among haplotypes and could promote hypervariability in toxin-encoding capacity of H. defensa isolates. Thus, the phages may enable H. defensa to mount a varied arsenal of toxins to defend aphid hosts against natural enemies, which vary among populations and over time (e.g., refs.…”
Section: The Apse-h Defensa-aphid Consortium As a Complex Mutualisticmentioning
confidence: 99%
“…A TTSS also appears to underlie infection of host cells by the symbionts of Sitophilus weevils (17) and by Photorhabdus species infecting nematodes (18). Such pathogenicity determinants are often transferred horizontally among enteric bacteria via bacteriophage vectors; these transfers have a role in transforming a nonpathogenic to a pathogenic strain (19)(20)(21). Because both pathogenesis and symbiosis share the requirement of bacterial establishment within host cells or tissues, additional mechanisms, already characterized in pathogens, may be incorporated into the symbiotic lifestyle or may underlie variation among symbionts in their effects on hosts.…”
mentioning
confidence: 99%
“…Several authors have shown that Stx2-encoding prophages are highly variable (Johansen et al, 2001) and present a high degree of heterogeneity in terms of induction levels (Muniesa et al, 2004a;Wagner et al, 1999). In agreement with these reports, we found that expression of stx 2 and stx 2 -related genes is heterogeneous in basal and in induced conditions, depending on the strain and on the stx 2 variant.…”
Section: Heterogeneous Expression Of Stx 2 Variantsmentioning
confidence: 99%
“…Various patterns of stx-phages have been described and since they present a wide range of DNA structures, restriction patterns, host spectra and morphology, they are considered to form a heterogeneous family (Unkmeir & Schmidt, 2000;Schmidt et al, 2000;Johansen et al, 2001). …”
Section: Introductionmentioning
confidence: 99%